Gastronomy: an overview of molecular gastronomy awareness - Faat, Farhan; Selahi, NurSyafiqah; Ramli, Rafidah Aida; Ali Tan, Zubaidah; Faat, Firmanshah (UiTM Cawangan Johor, 2022)
The world of gastronomy is no longer peculiar anymore for young culinarians and kitchen instructors. A current trend of modern cuisine incorporated with molecular gastronomy knowledge has widely been used all over the world. It is a study comprises of science and food for a better understanding. Varieties of food additives and equipment have been developed and used, as a result, most of the dish has been improvised and developed with surprise elements. In molecular gastronomy, science is a crucial subject needed to know and understand, others like art and creativity give additional value to the end product. Since Malaysia is a developing country and the understanding of molecular gastronomy knowledge is still in the introduction phase. Therefore this study will be conducted as a qualitative approach due to the lack of information and data in Malaysia.